Public health sans frontières: human rights NGOs and "stewardship on a global scale" - Murphy, Thérèse (Queen's University of Belfast, School of Law, 2011)
Part of a special issue: 'A symposium with Professor Roger Brownsword: super-stewardship in the context of public health', guest edited by Dr Mark Flear, and featuring papers by both Flear and Brownsword, as well as Dr John Coggon, Professor Soren Holm, Professor Tamara Hervey and myself